2002
DOI: 10.1177/004728750204100104
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Senior Traveler: An Australian Perspective

Abstract: Recently, the behavior of senior travelers has become an important area of interest because of its market size and potential for growth. This study describes a study profiling senior travelers according to their demographic and psychographic characteristics. Six market segments were used to highlight the differences that exist in terms of holiday attractions, travel motivations, and information sources used among senior travelers when planning and choosing a holiday. Seniors are shown not to be a uniform conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(45 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…More recently, Hsu et al (2007) employed indepth interviews with older individuals in China and identified several tourist motivations based on their physical, psychological, social, cultural, and economic conditions, and on their resulting desire to improve wellbeing, escape routines, socialize, and obtain knowledge, retain pride and patriotism, achieve personal rewards, and seek nostalgia. Despite mixed results in various contexts, previous studies have generally found that tourist motivations of older individuals are different from those of younger ones because the former undergo physical, psychological, and socioeconomic changes that have a considerable influence on their decisions and behaviors (Backman, Backman, & Silverberg, 1999;Cleaver et al, 1999;Horneman et al, 2002;Hsu et al, 2007;Huang & Tsai, 2003;Jang & Wu, 2006;Jang et al, 2009;Prayag, 2012;Shoemaker, 2000;Stone & Nichol, 1999;You & O'Leary, 1999).…”
Section: Tourist Motivations Of Older Individualsmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently, Hsu et al (2007) employed indepth interviews with older individuals in China and identified several tourist motivations based on their physical, psychological, social, cultural, and economic conditions, and on their resulting desire to improve wellbeing, escape routines, socialize, and obtain knowledge, retain pride and patriotism, achieve personal rewards, and seek nostalgia. Despite mixed results in various contexts, previous studies have generally found that tourist motivations of older individuals are different from those of younger ones because the former undergo physical, psychological, and socioeconomic changes that have a considerable influence on their decisions and behaviors (Backman, Backman, & Silverberg, 1999;Cleaver et al, 1999;Horneman et al, 2002;Hsu et al, 2007;Huang & Tsai, 2003;Jang & Wu, 2006;Jang et al, 2009;Prayag, 2012;Shoemaker, 2000;Stone & Nichol, 1999;You & O'Leary, 1999).…”
Section: Tourist Motivations Of Older Individualsmentioning
confidence: 98%
“…For example, Horneman, Carter, Wei, and Ruys (2002) suggested that in Australia, the tourism market for older individuals is not uniform and conservative, but divided into six segments in terms of preferred attractions and tourist motivations, namely enthusiasts, big spenders, pioneers, conservatives, indulgers, and Aussies. Huang and Tsai (2003) found that older individuals in Taiwan are likely to take trips for rest and relaxation and to meet people and socialize, and Jang and Wu (2006) identified knowledge-seeking and ego-enhancement motivations as the most important ones for these tourists.…”
Section: Tourist Motivations Of Older Individualsmentioning
confidence: 99%
“…The factors affecting seniors' preferences for travel participation and travel purchase decisions have received a special attention from academics. In this respect, demographic factors, specifically, the age variable (Batra, 2009) as well as the psychological factors (Horneman et al, 2002) were hypothesized to influence the travel choice of seniors (Reece, 2004). This line of investigation led some researchers to examine, for instance, the role of age in package tour participation (Wang et al, 2007), and to test the relationship between senior tourists' travel activities and their shopping behaviors (Littrell et al, 2004).…”
Section: Literature Review and Research Gaps In The Hospitality Litermentioning
confidence: 99%
“…The mature population constitutes a prime market for tourism 264 WANG, NORMAN, AND MCGUIRE research on pre-and postretirement travel plan changes was regarded as "the first serious investigation" of senior travel (Blazey, 1992, p. 772). In the succeeding years, researchers have investigated constraints to travel (Blazey, 1987;Huang & Tsai, 2003), differences between mature and young travelers (Anderson & Langmeyer, 1982;Norvell, 1985;Romsa & Blenman, 1989), general demographics (Blazey, 1992;Horneman, Carter, Wei, & Ruys, 2002;Romsa & Blenman, 1989), motivation (Guinn, 1980;Hagen & Uysal, 1991;Shoemaker, 1989Shoemaker, , 2000, psychological benefits (Hamilton & Taeff, 1986), resort visits (Uysal, Zimmerer, & Bonn, 1990), and uses of travel information (Capella & Greco, 1987). Neither are there any typical age standards (50+, 55+, 60+, or 65+) used in the field of leisure, tourism, and hospitality to define the older population (Norman, Daniels, McGuire, & Norman, 2001).…”
mentioning
confidence: 99%